A prospective study on the efficacy of platelet rich plasma in alopecia areata - Velappan, Ravichandran; Nallu, Kamalanathan; Ramasamy, Sindhuja; Chandrasekar, Muthusubramanian (International Journal of Research in Dermatology, 2019)
Background: Alopecia areata is an inflammatory auto-immune disease mainly affecting the scalp and other hair bearing areas. Platelet rich plasma contains concentrated platelets (more than that present in whole blood). Due to the presence of high concentration of growth factors, PRP is used in various conditions in the field of medicine and surgery. The aim of the study was to evaluate the efficacy of platelet rich plasma in alopecia areata. Methods: 20 patients, 16 male and 4 female with alopecia areata were enrolled in the study. PRP was injected in the alopecia sites for a total of 4 sessions every 28 days. Patients were followed in every month for 6 months and then at the end of one year. Pre and post treatment response was noted. Results: 13 patients responded well to treatment (65%), moderate response was seen in 3 (15%) patients and 4 patients showed no response (20%). 2 patients had relapse at the end of the study (10%). Conclusions: PRP was found to be an effective treatment modality for alopecia areata.